Risk factors for severe gastrointestinal toxicity in patients receiving palliative radiotherapy for metastatic bone tumors: association with the use of molecular-targeted agents. (22nd June 2020) - Murakami, Yuji; Kenjo, Masahiro; Ishikawa, Kazuki; Sakayauchi, Toru; Itasaka, Satoshi; Negoro, Yoshiharu; Jingu, Keiichi; Nishimura, Yasumasa; Nagata, Yasushi; Ogawa, Kazuhiko
Abstract: This study aimed to investigate whether the use of molecular-targeted agents could affect gastrointestinal (GI) toxicity in palliative radiotherapy (RT) for metastatic bone tumors in the abdominopelvic region. We collected data of patients who received palliative RT for bone metastases in the abdominopelvic region between 2013 and 2014 from six institutions. Data of 395 patients were collected and184 patients received molecularly targeted therapy, of whom 80 received vascular endothelial growth factor (VEGF)-targeted agents. For 556 lesions, 410 sessions of irradiation were undergone. GI toxicity of ≥G3 was observed in 3.8% of patients. The incidence rates of ≥G3 GI toxicity in patients without targeted agents use, in those using VEGF-targeted agents and in those using non-VEGF-targeted agents were 3.8, 7.5 and 1.0%, respectively. Regarding risk factors of the occurrence of ≥G3 GI toxicity, univariate analysis in all patients showed that a history of abdominopelvic surgery was a significant risk factor ( P = 0.01), and the use of VEGF-targeted agents showed a trend of high incidence ( P = 0.06). In patients using VEGF-targeted agents, both univariate and multivariate analysis showed that combined anticoagulant use ( P = 0.03 and 0.01) and agent use between 1 week before and after RT ( P = 0.046 and 0.03) were significant risk factors. In conclusion, the history of abdominopelvic surgery was associated with ≥G3 GI toxicity and the use of VEGF-targeted agents showed a trend for high incidence. When using VEGF-targeted agents, caution should be exercised in the combined use of anticoagulants and in the agent use between 1 week before and after RT.